Pengaruh Budaya Organisasi, Kepemimpinan Kepala Sekolah, dan Motivasi Kerja terhadap Kinerja Guru Yayasan Pendidikan Kristen Kota Medan - Kuras Purba (Pusat Riset dan Inovasi Nasional, 2025)
Teacher performance is influenced by various factors, including organizational culture, principal leadership, and work motivation. At the Medan City Christian Education Foundation, improving teacher performance is closely related to organizational culture as reflected in school traditions, principal leadership, and work motivation of each teacher. This study aims to analyze the influence of organizational culture, principal leadership, and work motivation on teacher performance in all schools of the Medan City Christian Education Foundation. The population of this study was 94 teachers at the Medan City Christian Education Foundation, Padang Bulan area. Sampling was carried out using cluster random sampling technique, resulting in 64 teacher respondents. The independent variables in this study include organizational culture, principal leadership, and work motivation, while teacher performance is the dependent variable. Data analysis was carried out using Multiple Linear Regression with the SPSS program. The results showed that organizational culture and work motivation had a positive and significant effect on teacher performance. Conversely, principal leadership did not have a positive and significant effect on teacher performance.